Co-designing a rural research practice partnership to design and support STEM pathways for rural youth - Bhaduri, Srinjita; Biddy, Quentin; Elliott, Colin Hennessy; Jacobs, Jennifer; Rummel, Melissa; Ristvey, John; Sumner, Tamara; Recker, Mimi (Theory & Practice in Rural Education, 2022)
Rural students, schools, and communities have unique challenges that hinder academic achievement, growth, and opportunities, compared to other locales. While there is a need to study this community more, there is also a pressing need to bring the local community members together to support the future generation of learners in developing pathways that lead them to future career opportunities. This article focuses on how a Research Practice Partnership (RPP) can be developed in rural communities to support STEM pathways for local middle-school youth. RPPs are often described as long-term collaborations between both researchers and practitioners in which the participating partners leverage research to address specific persistent problems of practice. We present findings from a developing design-based RPP focused on bringing community members and organizations together to co-design opportunities for underserved youth in rural mountain communities.